Plasmodium falciparum ookinete expression of plasmepsin VII and plasmepsin X. (December 2016) - Li, Fengwu; Bounkeua, Viengngeun; Pettersen, Kenneth; Vinetz, Joseph
Abstract Background Plasmodium invasion of the mosquito midgut is a population bottleneck in the parasite lifecycle. Interference with molecular mechanisms by which the ookinete invades the mosquito midgut is one potential approach to developing malaria transmission-blocking strategies.Plasmodium aspartic proteases are one such class of potential targets: plasmepsin IV (known to be present in the asexual stage food vacuole) was previously shown to be involved inPlasmodium gallinaceum infection of the mosquito midgut, and plasmepsins VII and plasmepsin X (not known to be present in the asexual stage food vacuole) are upregulated inPlasmodium falciparum mosquito stages. These (and other) parasite-derived enzymes that play essential roles during ookinete midgut invasion are prime candidates for transmission-blocking vaccines. Methods Reverse transcriptase PCR (RT-PCR) was used to determine timing ofP. falciparum plasmepsin VII (PfPM VII) and plasmepsin X (PfPM X) mRNA transcripts in parasite mosquito midgut stages. Protein expression was confirmed by western immunoblot and immunofluorescence assays (IFA) using anti-peptide monoclonal antibodies (mAbs) against immunogenic regions of PfPM VII and PfPM X. These antibodies were also used in standard membrane feeding assays (SMFA) to determine whether inhibition of these proteases would affect parasite transmission to mosquitoes. The Mann–Whitney U test was used to analyse mosquito transmission assay results. Results RT-PCR, western immunoblot and immunofluorescence assay confirmed expression of PfPM VII and PfPM X in mosquito stages. Whereas PfPM VII was expressed in zygotes and ookinetes, PfPM X was expressed in gametes, zygotes, and ookinetes. Antibodies against PfPM VII and PfPM X decreasedP. falciparum invasion of the mosquito midgut when used at high concentrations, indicating that these proteases play a role inPlasmodium mosquito midgut invasion. Failure to generate genetic knockouts of these genes limited determination of the precise role of these proteases in parasite transmission but suggests that they are essential during the intraerythrocytic life cycle. Conclusions PfPM VII and PfPM X are present in the mosquito-infective stages ofP. falciparum. Standard membrane feeding assays demonstrate that antibodies against these proteins reduce the infectivity ofP. falciparum for mosquitoes, suggesting their viability as transmission-blocking vaccine candidates. Further study of the role of these plasmepsins inP. falciparum biology is warranted.